(untitled) (Research, Society and Development, 2023)
Objective: to analyze the mediating effect of a healthy lifestyle on the mental health of participants in a Virtual Health Fair, during the COVID-19 pandemic. Methodology: Cross-sectional of 1,029 people aged 18 years and over. The Virtual Health Fair was organized as a tridimensional, and data were collected through a link on Google Forms, containing the sociodemographic data form, the Eight Natural Remedies Questionnaire (Q8RN), and the Common Mental Disorders questionnaire (SRQ-20). A Structural Equation Modeling (SEM) was performed. Results: Most participants were female (69%; n= 729), married (53.5%; n= 565), of higher education (43.2%; n= 458), and Adventist in religious affiliation (56.7%; n=597). On average, lifestyle was categorized as good by the Q8RN score (mean 56.61; SD 11.59), with a deficiency in the practice of exercise (5.87; 4.02). The Body Mass Index (BMI) was overweight on average (mean 26.02; SD 5.24). A prevalence of common mental disorders was 30.2% based on the SRQ-20 questionnaire. Conclusion: Results indicated that BMI, age, education, and religion had a strong protective effect (62%, p<0.05) for common mental disorders, mediated by healthy lifestyle. A better lifestyle, through the eight natural remedies, within the context of the COVID-19 pandemic, mediated the protective effects of lower BMI, older age, and Adventist religion on common mental disorders. The practice of healthy habits should be encouraged in promoting mental health during the current and future pandemics.